Constructing a web‐based health directory for adolescent men who have sex with men: Strategies for development and resource verification. Issue 3 (29th October 2021) - Drab, Ryan; Wolfe, James R.; Chavanduka, Tanaka; Bonar, Erin E.; Guest, Jodie L.; Hightow‐Weidman, Lisa; Castel, Amanda D.; J. Horvath, Keith; Sullivan, Patrick S.; Stephenson, Rob; Bauermeister, José
Abstract: Online health directories are increasingly used to locate health services and community resources, providing contact and service information that assists users in identifying resources that may meet their health and wellness needs. However, service locations require additional vetting when directories plan to refer vulnerable populations. As a tool included as part of a trial of a mobile life skills intervention for cisgender adolescent men who have sex with men (AMSM; ages 13–18), we constructed and verified resources for an online resource directory focused on linking young people to LGBTQ+ friendly and affirming local health and community social services resources. We collected information for 2301 individual directory listings through database and internet searches. To ensure the listings aligned with the project's focus of supporting young sexual minority men, we developed multiple data verification assessments to ensure community appropriateness resulting in verification of 1833 resources suitable for inclusion in our locator tool at project launch (March 2018). We offer lessons learned and future directions for researchers and practitioners who may benefit from adapting our processes and strategies for building culturally‐tailored resource directories for vulnerable populations.